Effect of isoprenaline on rabbit salivary glands at the electron microscopic level - Mansouri, S H; Mohammadpour, A A (The Indian Journal of Animal Sciences, 2012)
Major salivary glands were removed from seven adult female rabbits after daily injections of isoprenaline and compared with those of untreated controls. The parotid and the sub-mandibular glands increased four-and two-fold in wet weight, respectively, due to hypertrophy as well as hyperplasia. However, no apparent changes were seen in the sublingual glands. Following isoprenaline treatment tbe parotid acinar cells were markedly altered whereas ductal elements were apparently unchanged. In addition to hypertrophy the acinar cells were packed with many large electron-lucent secretory granules. The nuclei were compressed towards the base of the cells. In the submandibular gland the mucous acinar cells were most affected by isoprenaline treatment. The acinar cells which in controls were normally filled with a few electron-lucent secretory granules became enlarged and packed with many large electron-lucent secretory granules. Pronounced fusion of secretory granules resulted in many large units.